Short-time work: the German answer to the Great Recession - Brenke, Karl; Rinne, Ulf; Zimmermann, Klaus F. (Bonn, 2011)
"Short-time work was the "German answer" to the economic crisis. The number of short-time workers strongly increased in the recession and peaked at more than 1.5 million. Without the extensive use of short-time work, unemployment would have risen by approximately twice as much as it actually did. Short-time work has certainly contributed to the mild response of the German labor market to the crisis, but this is likely due to the country-specific context. Although the crisis has been overcome and employment is strongly expanding, modified regulations governing short-time work are still in place. This leads to undesired side effects."